Applications of vanadium, niobium, and tantalum complexes in organic and inorganic synthesis - Xu, Xinru (2023)
Organometallic catalysis is a powerful strategy in chemical synthesis, especially with the cheap and low toxic metals based on green chemistry principle. Thus, the selection of the metal is particularly important to plan relevant and applicable processes. The group VB metals have been the subject of exciting and significant advances in both organic and inorganic synthesis. In this Review, we have summarized some reports from recent decades, which are about the development of group VB metals utilized in various types of reactions, such as oxidation, reduction, alkylation, dealkylation, polymerization, aromatization, protein synthesis, and practical water splitting.